Factors Associated with Adolescent Premarital Sexual Behavior - Maria Faustina Arvidiani; Muntasir Muntasir; Amelya B. Sir (Journal of Health and Behavioral Science, 2023)
This study aims to analyze factors related to adolescent premarital sex behavior, namely intention, access to information, peer conformity, parental roles, acting situations and self-efficacy. The research was conducted at SMAK St. Familia Wae Nakeng, Lembor sub-district, West Manggarai Regency. The research conducted was an analytical survey using a cross-sectional study. The research subjects were SMAK St. students. Familia Wae Nakeng, numbering 88 teenagers. The sample selection used a proportioned stratified random sampling technique. Data analysis used bivariate analysis using the Chi-Square test. The results showed that intention, peer conformity, parental roles, acting situations and self-efficacy had a relationship with adolescent premarital sex behavior. while access to information has no relationship with premarital sex behavior among adolescents. It is hoped that the SMAK St. Familia Wae Nakeng can organizecommunication, information and education (IEC) programs regarding reproductive health in adolescents conducted by teachers or in collaboration with the BKKBN and local health centers.